Capacitance sensing and energy harvesting for wireless health monitoring system - Mustapha, Nurul Arfah Che; Alam, A.H.M. Zahirul; Khan, Sheroz; Azman, Amelia Wong (Institute of Electrical and Electronics Engineers, 2016)
In this work, a self-generated power capacitance measurement circuit for wireless health monitoring system is proposed. Hybrid energy from thermal and solar energy is expected to be used to supply the energy harvester. The present results has shown using low cost, off-the-shelf components, the capacitance measurement circuit is able to sense a linear capacitance range of 9.8 - 10.35 pF over 1.478 - 1.57 V output voltage range. This circuit also has low power consumption of 3.1 mW at frequency 40 kHz. This circuit is suitable for wireless health monitoring system.